2013
DOI: 10.1136/archdischild-2013-303672
|View full text |Cite
|
Sign up to set email alerts
|

To x-ray or not to x-ray? Screening asymptomatic children for pulmonary TB: a retrospective audit

Abstract: In contrast to the results from studies in adults, a CXR identified a small but noteworthy number of children with findings suggestive of pulmonary TB in the absence of clinical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…However, none of these participants had any signs of disease on detailed physical examination or were treated for active TB subsequently. Also, one of our previous studies has shown that chest x-ray changes potentially indicating active TB are rare in asymptomatic children screened after TB contact [43].…”
Section: Discussionmentioning
confidence: 94%
“…However, none of these participants had any signs of disease on detailed physical examination or were treated for active TB subsequently. Also, one of our previous studies has shown that chest x-ray changes potentially indicating active TB are rare in asymptomatic children screened after TB contact [43].…”
Section: Discussionmentioning
confidence: 94%
“…The researchers of one study conducted in South Africa, observed that children who were diagnosed with TB on CXR seemed to be asymptomatic [2729]. This shows that symptom based screening would miss some children with primary lung involvement on CXR.…”
Section: Discussionmentioning
confidence: 99%
“…1 [8,9]. Klassische Manifestationsarten der pulmonalen TB bei Erwachsenen wie Kavernen und Pleuraergüsse werden nur sehr selten beobachtet.…”
Section: Monatsschrift Kinderheilkunde 12 · 2015 1287unclassified